Pengaruh Lingkungan Kerja, Budaya Kerja, Dan Pengembangan Karir Terhadap Kinerja Karyawan Hotel Kurnia Bengkulu Utara. - Muhammad Bintang Azhari; Fauzan Fauzan; Janusi Waliamin (STIE AMKOP, 2023)
This study aims to determine how much influence the Work Environment (X1) Work Culture (X2) and Career Development (X3) have on Employee Performance (Y) Hotel Kurnia Bengkulu Utara. By using the Likert scale method by distributing questionnaires to respondents. The method used in this research is explanatory research